HPB P29 Pancreatoduodenectomy for suspected malignancy: postoperative nonmalignant histology confers increased risk of serious morbidity. (7th December 2022) - Russell, Thomas; Mavroeidis, Vasileios; Bowles, Matthew; Briggs, Christopher; Denson, Jemimah; Aroori, Somaiah
Abstract: Background: Pancreatoduodenectomy (PD) remains the treatment of choice for resectable cancers affecting the pancreatic head. It is the only curative-intent treatment option for pancreatic ductal adenocarcinoma (PDAC), the fourth leading cause of cancer-related death in Europe. Perioperative mortality following PD has fallen in recent years due to improvements to patient selection, operative technique and the centralisation of services. This is now less than 4.0% in high-volume centres. However, postoperative morbidity remains around 60% and relaparotomy is not uncommon. Not infrequently, a tissue diagnosis is not obtained preoperatively and radiologically distinguishing between benign, premalignant and malignant lesions can be challenging. Hence, a proportion of patients who are thought to have malignant disease preoperatively are ultimately found to have benign/premalignant histology postoperatively. It is unknown if this affects perioperative outcomes. This study aimed to compare the surgical outcomes of these patients with case-matched controls who had malignancy histologically confirmed postoperatively. Statistical analysis was designed to test the primary hypothesis that perioperative outcomes do not differ significantly between the two groups. Methods: A retrospective, paired case matched-control study was undertaken using a prospectively maintained database (01/01/2006–31/12/2020). Patients with suspected malignancy on preoperative imaging and a final histological diagnosis of a benign or premalignant disease were included. Forty-five cases were matched to confirmed malignant controls using the following criteria: age, gender, body mass index (BMI), American Society of Anesthesiologists (ASA) grade, preoperative serum bilirubin, application of neoadjuvant therapy (NAT), preoperative endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic biliary (PTC)-drainage, type of PD (standard Whipple's procedure or pylorus-preserving approach), absence of vascular resection or additional procedure, and type of pancreatic reconstruction (pancreatico-jejunostomy or pancreatico-gastrostomy). Matching was blinded to the measured outcomes, which included 30- and 90-day mortality and morbidity, quantified using the Clavien-Dindo system. Continuous variables both in preoperative matching and postoperative outcomes were analysed for distribution using the Shapiro-Wilk test. Fisher's exact test was used for categorical variables selected as part of the matching criteria. Significance was set at p<0.01. Continuous variables with non-normal distribution were analysed using the Mann-Whitney U test. Categorical variables from postoperative outcomes were analysed using either Fisher's exact test or the Chi-squared test. Results: A total of 609 PDs were performed. Overall morbidity and 90-day mortality rates were 49.9% and 3.1%, respectively. Forty-five patients (7.4%) were found to have undergone PD for suspected malignancy but ultimately found to have benign/premalignant histology. These cases were compared to 45 controls where malignancy was confirmed postoperatively. Matched characteristics demonstrated no significant difference between the benign/premalignant and malignant groups. Histology did not significantly affect 30-day mortality (5 vs 2, p=0.238), median length of stay (both 11 days, p=0.711), number of patients admitted to intensive care (both 29, p=1.00), or the number of days spent in intensive care (both one day, p=0.984). Furthermore, unplanned return to theatre (benign: 6, malignant: 4, p=0.502) and 90-day readmission rates (benign: 6, malignant: 5, p=0.138) were similar. Final histological diagnosis did not affect overall morbidity (both 28, p=1.00) but major morbidity (Clavien-Dindo grade III-V) was significantly higher in the benign/premalignant group (18 vs 8, p=0.035). Independently, clinically relevant postoperative pancreatic fistula (CR-POPF) was also more common in the benign/premalignant group (10 vs 2, p=0.013). This was despite the fact that pancreatic consistency and main pancreatic duct size did not significantly differ between the two groups. Conclusions: A not insignificant proportion of patients who undergo PD for suspected malignancy are ultimately found to have benign/premalignant histology. In our study, these patients had a significantly higher incidence of overall major morbidity when compared to those who had a malignant histological diagnosis confirmed. Patients with benign/premalignant disease were also found to have a higher incidence of pancreatic fistula, despite having similar pancreas texture and main pancreatic duct diameters compared with the malignant group. Future research should focus on developing methods that can accurately distinguish between malignant and non-malignant lesions preoperatively.